The Concept of Behavior Settings as a Criterion for the Design of Rehabilitation Centers for the Blind in the City of Bandung - Hansel Vince P; Hartanto Budiyuwono; Aldyfra L. Lukman (Jurnal Indonesia Sosial Teknologi, 2024)
Blind people who are included in the category of people with disabilities experience impairments and obstacles to their sense of sight. To be able to do orientation and mobility, blind people need information about environmental concepts and self-concepts. This of course requires training that is rehabilitative in nature. Sentra Wyata Guna Bandung is a building that functions as a rehabilitation and training center for blind people so that they can play an active role in community life. But in reality, the design of Sentra Wyata Guna has problems in terms of comfort and safety for blind people to do activities in it. This can hinder the rehabilitation and training process in it. This research aims to understand the behavior and needs of blind people for orientation and mobility with the concept of behavioral architecture; and find how the physical environment can stimulate the non-visual senses of blind people. This concept will be divided into five architectural design criteria based on behavioral setting theory. The study started with a literature review on the needs of blind people and behavioral concepts specific to blind people. Field data analysis detected the problems and potential of the Sentra Wyata Guna building.